Peroneus longus stretch reflex amplitude increases after ankle brace application - Cordova, M. L.; Ingersoll, C. D. (British Journal of Sports Medicine, 2003)
Background: The use of external ankle support is widespread throughout sports medicine. However, the application of ankle bracing to a healthy ankle over a long period has been scrutinised because of possible neuromuscular adaptations resulting in diminished dynamic support offered by the peroneus longus.